Pengaruh Pengalaman Auditor, Fee Audit dan Motivasi Auditor Terhadap Kualitas Audit - Junaedy Nainggolan; Fitrawansyah Fitrawansyah; Sopian Sopian (CV. ULIL ALBAB CORP, 2024)
This study aims to examine the influence of Auditor Experience, Audit Fees, and Auditor Motivation on Audit Quality. The unit of analysis in this research is individual auditors working at Public Accounting Firms (KAP) in Jakarta. For sampling purposes, the researcher selected the most accessible individuals who also had a close relationship with the researcher. The sample size consists of 109 individuals. This study employs linear regression analysis. The findings indicate that auditor experience does not significantly affect audit quality, while audit fees and auditor motivation have a positive and significant impact on audit quality.